Pengaruh Pengangguran dan Upah Minimum Regional terhadap Kemiskinan Melalui IPM sebagai Variabel Intervening: Studi pada 34 Provinsi di Indonesia - Dwie Belcha Nanda Damanik; Joko Suharianto (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This research aims to analyze the influence of unemployment and the Regional Minimum Wage (UMR) on poverty in 34 provinces in Indonesia with the Human Development Index (HDI) as an intervening variable. The high unemployment rate and minimum wage policy are considered to play a significant role in poverty conditions in the region. This research uses a path analysis approach with panel data from 2018 to 2022. The research results show that the unemployment rate has a positive influence on poverty, while the UMR shows a different influence in each province. HDI is proven to mediate the relationship between unemployment, UMR and poverty. This research contributes to the development of economic science and provides insight for the government and private sector in formulating poverty reduction policies.